Dimetallofullerene M2@C100 or carbide cluster fullerene M2C2@C98 (M = La, Y, and Sc): which ones are more stable?. Issue 26 (14th March 2017) - Mu, Lei; Bao, Xiaodi; Yang, Shumei; Kong, Xianglei
Abstract : The geometric and thermodynamic stability of the M2 C100 (M = La, Y, and Sc) series was systematically investigated using density functional theory calculations on the level of B3LYP/6-31G(d) ∼ Lanl2dz. Abstract : The geometric and thermodynamic stability of the M2 C100 (M = La, Y, and Sc) series was systematically investigated using density functional theory calculations on the level of B3LYP/6-31G(d) ∼ Lanl2dz. In all the cases, M2 @ D 5 (285913)-C100 isomers are the lowest-energy species. However, carbide endohedral fullerenes M2 C2 @ C 1 (230933)-C98 present excellent thermodynamic stabilities, except for those with La metal. The main product in electric arc experiments at temperatures lower than 3500 K for La2 C100 should be La2 @ D 5 (285913)-C100, which was successfully synthesized previously; for Y and Sc, the predicted main products in these experiments should be M2 C2 @ C 1 (230933)-C98 . Further analysis of the geometric structures of the M2 C100 series showed that the dimetallofullerenes M2 @C100 have greater effects on the shapes of cages than M2 C2 @C98 . These results provide some valuable guidance for the synthesis and characterization of large endohedral fullerenes including La, Y or Sc.